Food and feeding habit of insectivorous bats (Chiroptera) of Peechi-Vazhani wildlife sanctuary, western ghats, Kerala - Sachin K Aravind (Department of Wildlife Sciences, College of Forestry, 2014)
A field study was conducted to understand the food, feeding habit and food preferences of insectivorous bats (Microchiroptera) of Peechi-Vazhani Wildlife Sanctuary, Western Ghats, Kerala. The study was conducted from May 2013 to February 201~ in the selected roosts. Insectivorous bat species studied were Rhinolophus rouxii, Hipposideros speoris and Hipposideros ater. The method adopted were faecal matter analysis. Faecal matter were collected for each species of insectivorous bats once in a month throughout the study period. These pellets were analyzed in laboratory to identify food components and percent volume. From the faecal matter analysis Rhinolophus rouxii were found to be feeding on eleven insect orders (Lepidoptera, Coleoptera, Diptera, Hymenoptera, Hemiptera, Isoptera, Orthoptera, Odonata, Mantodea, Neuroptera and Ephemeroptera) and spiders (Araneae), Hipposideros speoris were found to be feeding on ten insect orders (Lepidoptera, Coleoptera, Diptera, Hymenoptera, Hemiptera, Isoptera, Orthoptera, Odonata, Neuroptera and Ephemeroptera) and spiders (Araneae). And the Hipposideros ater was found to be feeding on eight insect orders (Lepidoptera, Coleoptera, Diptera, Hymenoptera, Hemiptera, Isoptera, Orthoptera and Odonata) and spiders (Araneae). Lepidoptera was the most fed insect orders by all the three insectivorous bats under study. Coleoptera was the second most fed insect order and Diptera